1995
DOI: 10.2214/ajr.164.6.7754901
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-spray pharmacomechanical thrombolysis of thrombosed hemodialysis access grafts: long-term experience and comparison of original and current techniques.

Abstract: OBJECTIVE.Pulse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(50 citation statements)
references
References 6 publications
4
44
0
2
Order By: Relevance
“…Angioplasty early in the procedure does result in more rapid thrombolysis times than we have reported in this paper [17]. However, at the time this study was performed, we were not doing angioplasty until there was minimal residual thrombus within the graft.…”
Section: Discussionmentioning
confidence: 78%
“…Angioplasty early in the procedure does result in more rapid thrombolysis times than we have reported in this paper [17]. However, at the time this study was performed, we were not doing angioplasty until there was minimal residual thrombus within the graft.…”
Section: Discussionmentioning
confidence: 78%
“…However, the pulmonary embolisms caused by mechanical techniques in these cases were not clinically important. The authors further argued that pulmonary embolisms also occur with pulse-spray pharmacomechanical thrombolysis (18)(19)(20). Filters with a fine net, not the usual temporary filters, may be needed to confirm the presence of small pulmonary embolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse-spray thrombolysis has been used to treat thrombotic occlusion of the hemodialysis shunt and in peripheral artery disease. [11][12][13][14] It is the combination of the pharmacological effect of the thrombolytic agent and the mechanical destruction of the thrombus by the compulsive jets from side holes of the infusion catheter that make the technique more effective than pharmacological thrombolysis alone, and lead to rapid recanalization. 22 Saito et al showed that pulse-spray thrombolysis is effective in the critical situation of an acutely obstructed coronary artery; they successfully treated patients with subacute thrombosis of an implanted coronary artery stent, a large clot in the infarct-related artery, and a thrombotic complication of intravascular ultrasound.…”
Section: Discussionmentioning
confidence: 99%